Effects of one-week intake of different edible oils on the urinary proteome of rats - Su, Yan; Gao, Youhe (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the effects of different edible oils on the rat body, we analyzed alterations in the urinary proteome and post-translational modifications (PTMs) following a one-week intake of olive oil, butter, lard, hydrogenated vegetable oil, and rapeseed oil.MethodsThirty male Wistar rats (7 weeks old, ~200 g) were randomly allocated into six groups (n = 5 per group). Group A served as the control group, while groups B-F were administered different edible oils. The daily intakes were calculated, respectively, according to the “2015–2020 Dietary Guidelines for Americans” and the “Dietary Guidelines for Chinese Residents.” Urine samples collected after 1 week were analyzed using label-free quantitative proteomics via LC–MS/MS. Differentially expressed proteins and differential post-translational modifications in the urinary proteome were screened for functional analysis.ResultsAll edible oil groups exhibited significant alterations in metabolic pathways, with distinct proteomic profiles observed across oil types, but there were few common differentially expressed proteins among different groups. In addition, the olive oil group and the butter group were enriched with many biological pathways related to the nervous system, and the rapeseed oil group produced more differentially expressed proteins and biological pathways related to immunity.ConclusionThe urinary proteome of rats showed significant changes after one-week intake of edible oils, and the effects of various edible oils on the rat urinary proteome were different from each other. This effect is comprehensive and multi-dimensional at the level of the rat body. The changes in post-translational modifications of the proteome were relatively small.